Interpretation of Political Inclination in Online Newspapers: An Ideological Disposition through Transitivity Analysis - Saira Asad; Siti Noor Fazelah Binti Mohd Noor; Lutfan Bin Jaes (Master Program in Linguistics, Diponegoro University, 2021)
The language of newspapers depicts the ideology of news institutions. The online alternative Malaysian newspaper, ‘Malaysiakini’, and mainstream online newspaper ‘The New Straits Times (NST)’ had shown different stances through grammatical terms during 100 days of Pakatan Harapan (PH), which leads to uncovering the news institutions’ ideology by observing their past performances and current representation. Norman Fairclough’s (1995) Critical Discourse Analysis (CDA) was employed on hard news reports, which were analyzed with the Halliday Systemic Functional Linguistics (SFL) tool. ‘Pakatan Harapan (PH)’ as a political party was found as main ‘doer’ in ‘100 days’ performance after winning election 2018 in both newspapers through their linguistic stances, which were collected from 5 (3,334 words) news reports from ‘Malaysiakini’ and 3 (2,478 words) from ‘NST’ based on social actor’s performances on 17th and 18th August 2018. ‘Malaysiakini’ had maintained its neutral stance, while ‘The New Straits Times’ had shifted its stance towards PH in their ruling government.